Chemical Punch Packed in Venoms Makes Centipedes Excellent Predators - Yang, Shilong; Liu, Zhonghua; Xiao, Yao; Li, Yuan; Rong, Mingqiang; Liang, Songping; Zhang, Zhiye; Yu, Haining; King, Glenn F.; Lai, Ren (Molecular & cellular proteomics, 2012)
Centipedes are excellent predatory arthropods that inject venom to kill or immobilize their prey. Although centipedes have long been known to be venomous, their venoms remain largely unexplored. The chemical components responsible for centipede predation and the functional mechanisms are unknown. Twenty-six neurotoxin-like peptides belonging to ten groups were identified from the centipede venoms, Scolopendra subspinipes mutilans L. Koch by peptidomics combined with transcriptome analysis, revealing the diversity of neurotoxins. These neurotoxins each contain two to four intramolecular disulfide bridges, and in most cases the disulfide framework is different from that found in neurotoxins from the venoms of spiders, scorpions, marine cone snails, sea anemones, and snakes (5S animals). Several neurotoxins contain potential insecticidal abilities, and they are found to act on voltage-gated sodium, potassium, and calcium channels, respectively. Although these neurotoxins are functionally similar to the disulfide-rich neurotoxins found in the venoms of 5S animals in that they modulate the activity of voltage-gated ion channels, in almost all cases the primary structures of the centipede venom peptides are unique. This represents an interesting case of convergent evolution in which different venomous animals have evolved different molecular strategies for targeting the same ion channels in prey and predators. Moreover, the high level of biochemical diversity revealed in this study suggests that centipede venoms might be attractive subjects for prospecting and screening for peptide candidates with potential pharmaceutical or agrochemical applications.